Eksplorasi Problem Based Learning dalam Menumbuhkan Kesadaran Sains Siswa Sekolah Dasar tentang Bahaya Kimia pada Makanan - Tamarin, Vina; Fatonah, Siti; Aulia, Syarifah Risma (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to explore the application of Problem-Based Learning (PBL) in fostering elementary school students' scientific awareness regarding the dangers of chemical substances in food. This research employs a qualitative approach with a qualitative descriptive analysis method. Data collection was conducted through interviews focused on a teacher at a public elementary school in Cianjur Regency, West Java. The instrument used was in-depth interviews. The data analysis technique employed includes data condensation, data presentation, and drawing conclusions. The results indicate that PBL is effective in enhancing students' understanding of the dangers of chemical substances, thereby fostering scientific awareness among elementary school students. The observed indicators include students' ability to explain the effects of chemicals, provide real-life examples, and actively participate in group discussions. PBL also facilitates collaborative, critical, and experiential learning, which helps instill an awareness of the importance of choosing healthy food. This study recommends the broader implementation of PBL to enhance students' scientific and health awareness from an early age.